Influence of ring traveller weight and coating-on hairiness of acrylic yarns - (:unkn) unknown (INST CHEMICAL FIBRES, 2002)
This study involves the results of an investigation concerning the influence of ring travellers of different weights, types and coatings on the hairiness of acrylic yarns spun from microfibres. 30 tex yarn was produced using C-type travellers with a twist factor of alpha(tex)=31.6. Travellers of 8 different weights and 4 different coatings were used working with two spindle speeds of 7000 rpm and 10,000 rpm. Yarn hairiness was evaluated with the use of a Shirley Yarn Hairiness Tester. The values of tension, breakage rate, count, twist, evenness, elongation and tensile strength of the yarn produced were measured. In addition the yarns were knitted into fabrics to observe and evaluate pilling. Some conclusions were drawn considering yarn hairiness.
Keywords: hairiness; acrylic yarn; spinning; traveller; pilling